Circularly polarised patch array antenna based on reactive impedance surface. Issue 14 (17th September 2018) - Zhang, Zhiyi; Chen, Wan; Fu, Jiahui; Li, Peng; Lv, Bo; Wang, Zhefei
Abstract : In this study, a circularly polarised (CP) patch array antenna based on reactive impedance surface (RIS) is presented. The proposed 4 × 4 patch array antenna possesses a RIS layer which is utilised to replace the conventional ground plane in order to enhance the bandwidth. Meanwhile, patches are cut with two diagonal corners and a rectangular slot for the fulfilment of wideband CP radiation and fed by a one‐to‐sixteen network simultaneously. Furthermore, in order to explain the effect of RIS in the axial ratio (AR), the CP antenna elements with (or without) RIS are designed. There is the same trend in simulated and measured results. Measured results show the proposed antenna exhibits good performances, such as wideband impedance matching, low AR, high gain. It is testified that pure CP radiation and symmetry broadside patterns are achieved in a wide frequency band, indicating the proposed antenna can exhibit significant application in global satellite communication systems and 5G Wi‐Fi application.